CGRP, PD-1 and PD-L1 as Biomarkers for PICC-Related Bloodstream Infections in Breast Cancer Patients - Jun-Tao Tan MD; Lili Hu MD; Qi-Hua Jiang MD; Hai Hu MD; Zhi Yang MD; Zhi-Hua Li PhD; Ping-Hua Hu MD (Technology in Cancer Research & Treatment)
Introduction Peripherally inserted central catheter (PICC)-related bloodstream infections (BSIs) are severe complications in breast cancer patients undergoing chemotherapy. This study evaluated the diagnostic potential of calcitonin gene-related peptide (CGRP), programmed cell death protein-1 (PD-1), and its ligand (PD-L1) as biomarkers for PICC-related BSIs. Methods A total of 384 breast cancer patients with PICC placement were retrospectively identified from medical records, of these, 78 developed BSIs and 306 did not. Serum levels of CGRP, PD-1, and PD-L1 were measured using enzyme-linked immunosorbent assay (ELISA) and quantitative polymerase chain reaction (qPCR), respectively, to evaluate their potential as diagnostic biomarkers for BSIs. Blood cultures were performed to confirm infections and identify pathogens. Results The BSIs group showed significantly lower CGRP and PD-L1 levels, and higher PD-1 expression and PD-1/PD-L1 ratios compared to the non-BSIs group (all P < 0.001). Receiver operating characteristic (ROC) curve analysis showed area under the curve (AUC) values of 0.84 for CGRP, 0.77 for PD-1, 0.70 for PD-L1, and 0.86 for the PD-1/PD-L1 ratio. Combined detection achieved an AUC of 0.96, with 88% sensitivity and 92% specificity. Gram-negative bacteria (59.8%) were the predominant pathogens, with Escherichia coli (29.3%) being the most common. Conclusion CGRP alone showed strong diagnostic utility, but combining CGRP, PD-1, and PD-L1 markedly enhanced accuracy. ELISA and qPCR detection of these markers provides results within hours, enabling earlier diagnosis than conventional blood cultures.